Arquitetura e industrialização: influência da Filosofia "Lean" nos processos de gestão da construção. - Coelho, Gustavo Modesto (2020)
This paper aims to discuss the terms and characteristics related to the industrialization of buildings, supported by a lean view of processes (Lean Construction), aims to point a new perspective on the productive relationship, as well as the tools that support the management of a project and its steps. The prefabrication of components has long been discussed and applied as an alternative to the conventional method of construction, since it has inefficiencies of all kinds. However, for us to understand these relationships, it is necessary to analyze the path and development of what was proposed in the national field based on the experiences and concepts developed worldwide, since Brazil is immature in the methodology applied to industrialized construction. This dissertation aims to systematically cover the works that represent a change in the rationalization characteristics of the architect João Filgueiras Lima, in order to support the case studies based on his experiences with the factory. The case studies reflect three different eras and buildings that have become milestones in industrialized architecture due to the high degree of rationalization present there. The chosen works reflect different perspectives, panoramas, architects and degrees of industrialization in order to broaden the discussion about industrialized architecture and the lean philosophy of buildings. The relevance of this dissertation unfolds on the systemic view and leads to the argument of the best practices to be aspired in the industrialization of architecture, not those linked to rigid systems, but one that is justified by the inserted environment